Pengaruh iradiasi sinar gamma terhadap fertilitas Sternochetus frigidus (Fabricius) (Coleoptera: Curculionidae) pada mangga kuini - Ade Syahputra; Mustopha Ahad; Abdurakhman Abdurakhman; Joni Hidayat; Djoko Prijono; Indah Arastuti Nasution (Perhimpunan Entomologi Indonesia, 2020)
One of the recognized and safe quarantine treatments for consumers is the use of gamma-ray irradiation [60Co] at a recommended dose requested by the destination country or international agency. The purpose of this study was to test the effectiveness of a generic dose of gamma ray irradiation for sterilizing mango pulp weevil Sternochetus frigidus (Fabricius) on mangoes cv kuini (Mangifera odorata). A total of 300 kg pulp-weevil-infested mango fruits was collected from West Sumatra and Lampung. First experiment was conducted on April to irradiate fruits collected from West Sumatera and second experiment was on May to irradiate fruits collected from Lampung. In each treatment, a box containing 6-8 M. odorata fruits was irradiated with gamma-ray at doses of 50, 100, 150, 200, 300, 400 Gy with three replications. The treatment of gamma-ray irradiation could reduce feeding activity, normal life of insect, egg production and increase mortality of adults. The results of the first and second experiments showed that gamma ray irradiation was able to influence the development of pupae and adults. There were differences in the normal development of adults in the two experiments. The number of normal development of adults on first experiment was higher than on the second experiment. The irradiated pupae at dose of 100 Gy successfully develop to be adults but the adults are unable to produce eggs. Adults irradiated at 150 Gy are still able to lay eggs with the average of 6 eggs (first experiment) and 2,3 larvae (experiment II), 150 Gy average 6 eggs and do not hatch. Doses at 200 Gy no eggs were produced.